Growth and oscillation theories of differential polynomials - Belaıdi, Benharrat; El Farissi, Abdallah (Novi Sad J. Math, 2009)
In this paper we investigate the complex oscillation and the growth of some differential polynomials generated by the solutions of the differential equation f''+ A1 (z) f'+ A0 (z) f= F, where A1 (z), A0 (z)(≡ 0), F are meromorphic functions of finite order.
Keywords: Linear differential equations; Meromorphic solutions; Hyper order; Exponent of convergence of the sequence of distinct zeros; Hyper exponent of convergence of the sequence of distinct zeros